The impact of cue and preparation prompts on attention guidance in goal-directed tasks - Li, Yahui; You, Yimeng; Yu, Baobao; Lu, Yue; Zhou, Huilin; Tang, Min; Zuo, Guokun; Xu, Jialin (Frontiers in Human Neuroscience, 2024)
In goal-directed tasks, visual prompts before the appearance of goals can make people ready in advance, which helps them to complete the movement better, and the presentation type of the visual prompt is very important. In previous studies, it has not been clear how different types of visual prompts guide attention in goal-directed tasks. According to the characteristics of goal-directed tasks, our research designed three different prompts: the cue prompt (featuring static arrow), the preparation prompt (involving dynamic countdown), and the combination prompt of cue and preparation information (simultaneously incorporating arrow and countdown). We used event-related potential components (CNV and P300) and graph theory indicators (clustering coefficient and characteristic path length) under the brain function connection to analyze the attention state of the brain. The results showed that the combination prompts better guided the participants' sustained attention during the prompt stage, making them well prepared for the movement. Thus, after the target appeared, the participants had better executive control and achieved a faster response to the target. However, under the combination prompt, the participants consumed more attention resources during the prompt stage.Therefore, for the participants with impaired cognitive function, cue prompts or preparation prompts can be considered, which also play a role in guiding the participants' attention and helping them make motor preparations when less attention resources are consumed. This study provides a neurophysiological and behavioral foundation for the design of visual prompts in goal-directed tasks.